Thirty-year trends and outcome of isolated versus combined group 2 pulmonary hypertension after cardiac transplantation - Nasri, Amine; Dupuis, Jocelyn; Carrier, Michel; Racine, Normand; Parent, Marie-Claude; Ducharme, Anique; Fortier, Annik; Hausermann, Leslie; White, Michel; Tremblay-Gravel, Maxime (Frontiers in Cardiovascular Medicine, 2022)
Aim To investigate the effect of the new definition of pulmonary hypertension (PH) and new pulmonary vascular resistance (PVR) thresholds on the prevalence, clinical characteristics, and events following cardiac transplantation (CTx) over 30 years. Methods Patients who underwent CTx between 1983 and 2014 for whom invasive hemodynamic data was available were analyzed (n = 342). Patients transplanted between 1983 and 1998 were classified as early era and those transplanted between 1999 and 2014 were classified as recent era. Group 2 PH was diagnosed in the presence of a mean pulmonary artery pressure (mPAP) > 20 mmHg and pulmonary capillary wedge pressure (PCWP) > 15 mmHg. Isolated post capillary PH (Ipc-PH) was defined as PVR ≤ 2 wood units and combined pre and post capillary PH (Cpc-PH) was defined PVR > 2 wood units. Moderate to severe PH was defined as mPAP ≥ 35 mmHg. The primary outcome was 30-day mortality and long-term mortality according to type and severity of PH. Proportions were analyzed using the chi-square test, and survival analyses were performed using Kaplan-Meier curves and compared using the logrank test. Results The prevalence of PH in patients transplanted in the early era was 89.1%, whilst 84.2% of patients transplanted in the recent era had PH (p = 0.3914). There was no difference in the prevalence of a pre-capillary component according to era (p = 0.4001), but severe PH was more common in the early era (51.1% [early] vs 38.0% [recent] p = 0.0151). Thirty-day and long-term mortality were not significantly associated with severity or type of PH. There was a trend toward increased 30-day mortality in mild PH (10.1%), compared to no PH (4.4%) and moderate to severe PH (6.6%; p = 0.0653). Long-term mortality did not differ according to the severity of PH (p = 0.1480). There were no significant differences in 30-day or long-term mortality in IpcPH compared to CpcPH (p = 0.3974 vs p = 0.5767, respectively). Conclusion Over 30 years, PH has remained very prevalent before CTx. The presence, severity, and type (pre- vs post-capillary) of PH is not significantly associated with short- or long-term mortality.